O społeczno-politycznych źródłach złego stresu i jego edukacyjnych skutkach - Olubiński, Andrzej (Studia Edukacyjne, 2019)
The main problem of considerations concerns the relationships and dependencies between selected socio-political factors as stressors and specific reactions to them of selected categories of people and groups, analysed in terms of educational processes. The author is especially interested in the stressful and educational role of human participation in the system of corporate trade as the source of artificially created needs connected with continuous shopping and multiplying material goods. The second stress factor analysed below is the character of state power exercised by politicians, with the particular role of its distortion towards authoritarian relations. The final kind of synthetic summary of the above deliberations is an attempt of critical evaluation of the educational role of stress caused by the authoritarian school. And although the discussed stress factors the author attempts to refer to individual behaviours, taking into account, for example, the concepts of human nature, age and institution (e.g. school), the conclusions and findings resulting from these analyses are also more general. Their essence relates to the thesis that regardless of individual behaviours in a stressful situation, generally negative stressors, such as the impact of corporate economy, pathological character of exercising authority or authoritarian school usually shape negative behaviour, including mainly authoritarian personalities.